(untitled) (Stamford Journal of Microbiology, 2023)
Staphylococcus aureus causes significant epidemiologic and therapeutic challenges with various skin and soft tissue infections, the main forms of disease manifestation. The public health importance of this organism has been heightened by the emergence and spread of species that are resistant to treatment usually referred to as methicillin-resistant S. aureus (MRSA). This study was carried out to detect mecA and mecC genes in phenotypically determined MRSA isolates. Nasal swab samples of the subjects were cultured on mannitol salt agar and the isolates were identified as S. aureus using a combined morphological and biochemical characteristic. Antibiotic susceptibility profile was performed using the disk diffusion susceptibility method whilst phenotypic detection of MRSA isolates was by Cefoxitin disk diffusion method as per CLSI guidelines. Genomic DNA was extracted from the isolates using commercial kits. The extracted DNA was subjected to multiplex PCR to amplify the 163-bp and 188-bp fragment of the mecA and mecC genes respectively in a Pielter thermal cycler. The susceptibility pattern of MRSA isolates showed that the organisms were highly resistant to Augmentin 29 (93.5%), ceftazidime 18 (58.1%), Streptomycin 19 (76%) whilst high levels of susceptibility were seen for Ofloxacin 27 (87.1%), Levofloxacin 28 (90.3%), and Gentamicin 24 (77.4%). The antibiotic resistance profiles in MRSA isolates were recorded as follows: ciprofloxacin 6 (16.2%), Augmentin 32 (86.4%), erythromycin 13 (35.1%), Ceftazidime 22 (59.4%). Of the 10 MRSA isolates that were subjected to PCR, one isolate was found to harbor the 188-bp of mecC gene whilst mecA was absent from the screened isolates. The detection of mecC MRSA in the present study highlights the diagnostic importance of screening for mecC in mecA negative MRSA. We suggest that surveillance for MRSA should include screening for mecC gene where mecA is not detected in resistant isolates. Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 6-10